The concept of youth political activity. (The Peerian Journal, 2024)
Increasing youth activity as a law of social development Today, the changes in the social situation of various groups of the population do not exclude youth, which is considered a “constant disseminator of progressive ideas.” Young people are a special socio-demographic group that is experiencing growth and development and whose situation is determined by the socio-political situation of society. This article focuses on that